Faktor-Faktor Yang Memengaruhi Struktur Modal Perusahaan Manufaktur Terdaftar Di BEI Periode 2014-2017 - Nathania Michaela Alvina, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effects of growth opportunity, profitability, assets tangibility, and liquidityoncapital structurein manufacturing industries listed in Indonesian Stock Exchange during the period of 2014-2017. This research used 64samples of manufacturing companies that have been previously selected using purposive sampling method with total of 256 data for four years. The data used were secondary data in the form of financial information from the corporate annual reports. This research data was processed using EViews 10 Student Version.The result of this research shows that profitability and liquidity have significant effect on capital structure while growth opportunity and assets tangibility do not have significant effect on capital structure